Cardiac-Related Lesions in Newly Diagnosed Patients With Acute Leukemia: A Chinese Population-Based Real-World Study - Xiao, Wei; Ma, Linlu; Shang, Yufeng; Yang, Fuwei; Tan, Yuxin; Chen, Guopeng; Wu, Jinxian; Liang, Yuxing; Rouzi, Tuerxunayi; Wang, Qian; Zhang, Nan; Zhou, Fuling (Frontiers in Medicine, 2022)
The relationship between newly diagnosed acute leukemia (AL) and heart-related lesions remains unclear. This study aimed to investigate baseline cardiac function and risk of cardiovascular diseases (CVDs) in patients with new-onset AL, and provide data on cardiac management strategies for patients with AL. We retrospectively collected data on baseline characteristics, echocardiography, and biochemical blood indicators (e.g., myocardial enzymes) from 408 patients, 200 with newly diagnosed AL, 103 with coronary artery disease (CAD), and 105 controls from January 1, 2015 to August 31, 2019. The creatine kinase isoenzyme myocardial band, lactate dehydrogenase, highly sensitive troponin-I, and B-type natriuretic peptide levels and left ventricular internal diameter (LVID) were significantly higher in patients with newly diagnosed AL than in the control group. The degree of cardiac damage was lower in newly diagnosed AL patients than in CAD patients. The best predictor of heart damage was LVID (AUC [area under the curve] = 0.709; 95% CI [confidence interval]: 0.637–0.781; p < 0.001), and independent prognostic risk factors were age and ejection fraction (HR [hazard ratio] = 1.636; 95% CI: 1.039–2.575; p = 0.033). The ratio of leukemia blasts among patients with AL was positively correlated with cardiac damage. Our data indicated that newly diagnosed AL patients had certain myocardial damage before treatment. Clinicians need to pay attention to these manifestations, which may be related to the prognosis.